Influence of cooling medium on the microstructure and hardness of metastable Ti-15Mo-8Fe alloy - Moshokoa Nthabiseng; Makhatha Elizabeth; Raganya Lerato; Makoana Nkutwane Washington; Chauke Hasani; Diale Ramogohlo; Phasha Maje (MATEC Web of Conferences)
Mechanical properties of metastable β-titanium (Ti) alloys are affected by factors such as the composition of the alloying elements, the process technique and phases formed due to different cooling medium after heat treatment. The effect of high iron (Fe) content in Ti-15Mo alloy under different cooling medium on the microstructural characteristics and hardness are investigated in this study. The alloy with a composition of Ti-15Mo-8Fe (wt%) was fabricated by melting in a commercially arc melting furnace and they were heat treated in a muffle furnace at 1100°C with 1hr holding time. The heat treated samples were subjected to various cooling medium such as water quench (WQ), Air cooling (AC) and furnace cooling (FC). Different characterization techniques such as the X-ray diffractometer (XRD) was used to analyse the presence of the phases, the Optical Microscope (OM) was used to analyse the microstructure and the Micro-Vickers hardness tester was used to measure the hardness. The XRD peaks revealed Fe·Ti·O2 oxides and β phase only in WQ condition, peaks in AC illustrated only β phase, FC samples showed both the β and the α phases only and B2 peaks in As-cast. The OM of WQ sample demonstrated large equiaxed β grains with pores around the grain boundaries, whereas the AC and FC illustrated medium grains with substructures and small grains with precipitates around the grain boundaries respectively and the OM micrographs of As-cast displayed dendritic structure only. The AC sample showed the highest hardness followed by the As-cast, then the WQ and the lowest hardness was seen in FC sample.